Edge‐Site Engineering of Defective Fe–N4 Nanozymes with Boosted Catalase‐Like Performance for Retinal Vasculopathies (Adv. Mater. 39/2022). Issue 39 (27th September 2022) - Zhang, Ruofei; Xue, Bai; Tao, Yanhong; Zhao, Hanqing; Zhang, Zixia; Wang, Xiaonan; Zhou, Xinyao; Jiang, Bing; Yang, Zhenglin; Yan, Xiyun; Fan, Kelong
Abstract : High‐Performance Nanozymes In article number 2205324, Zhenglin Yang, Xiyun Yan, Kelong Fan, and co‐workers report a high‐performance catalase‐like iron single‐atom nanozyme prepared by edge‐site engineering. Hierarchical mesoporous and edge‐hosted atomic sites are formed during the pyrolysis process, enabling efficient catalytic decomposition of H2 O2 into O2 and H2 O. Based on the catalase‐like activity, effective treatment of retinal vasculopathies is realized by intravitreal administration of the nanozyme.